2000
DOI: 10.1097/00006565-200012000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Capnography during sedation/analgesia in the pediatric emergency department

Abstract: Commonly used agents for pediatric sedation result in significant increases in ETCO2. ETCO2 is a useful adjunct in assessing ventilation and may serve as an objective research tool for assessing different sedation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 13 publications
0
40
2
Order By: Relevance
“…A change in ETCO 2 level R10 mm Hg from the presedation baseline and an intrasedation ETCO 2 level %30 mm Hg or R50 mm Hg were considered investigational acute respiratory events. 4,[6][7][8][9] For observed acute respiratory events, the type and time of the acute respiratory events were entered into the monitor along with the clinical assessment and vital sign data at that time.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…A change in ETCO 2 level R10 mm Hg from the presedation baseline and an intrasedation ETCO 2 level %30 mm Hg or R50 mm Hg were considered investigational acute respiratory events. 4,[6][7][8][9] For observed acute respiratory events, the type and time of the acute respiratory events were entered into the monitor along with the clinical assessment and vital sign data at that time.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Pulse oximetry measures oxygen saturation but this only provides a late alarm and may be adversely affected after an unreasonable depression has occurred in respiration. Mcquillen et al [2] and Tobias [3] both found that end-tidal CO 2 monitoring enabled the early detection of respiratory depression. Whilst Miner et al [4] concluded that end-tidal CO 2 enhanced safety and detected subclinical respiratory depression.…”
Section: ó 2009 the Association Of Anaesthetists Of Great Britain Andmentioning
confidence: 99%
“…There is a strong association between low spine anomalies and genitourinary and colorectal structures [1,2]. Genitourinary, colorectal, and musculoskeletal systems are all of mesodermal origin and develop at the same time in the embryo, so that any insult inducing congenital vertebral malformations during organogenesis may also lead to congenital genitourinary or colorectal abnormalities [2].…”
Section: ó 2009 the Association Of Anaesthetists Of Great Britain Andmentioning
confidence: 99%
See 2 more Smart Citations